Nickel-Catalyzed Multicomponent Coupling of Alkyne, Buta-1,3-diene, and Dimethylzinc under Carbon Dioxide - Mori, Yasuyuki; Mori, Takamichi; Onodera, Gen; Kimura, Masanari (Synthesis, 2014)
A nickel catalyst promoted the coupling of alkynes with buta-1,3-diene and dimethylzinc under carbon dioxide to provide (5E,8Z)-2-vinyldeca-5,8-dienoic acids with high regio- and stereoselectivity.
Keywords: nickel; alkyne; carbon dioxide; butadiene; dimethylzinc